Cost-effectiveness of symptom monitoring with patient-reported outcomes during routine cancer treatment. (March 2018) - Nixon, N.A.; Spackman, E.; Clement, F.; Verma, S.; Manns, B.
Highlights: Symptom burden is high in patients undergoing therapy for solid tumours. A randomized study demonstrated web-based symptom monitoring improves outcomes, including overall mortality. In cost-utility analysis, this tool led to an incremental cost-effectiveness ratio of 13, 450.00 per quality-adjusted life-year. Web-based symptom monitoring tools should be considered as a cost-effective means to improving patient outcomes. Abstract: Background: A recent study reported that inclusion of a patient-reported outcome (PRO) tool for symptom monitoring during routine cancer treatment for patients with advanced or metastatic disease leads to improved health-related quality of life, decrease in emergency room visits and hospitalization, and improvement in overall survival. Whether the implementation of such a tool would be cost-effective remains uncertain. Objectives and decision problem: The purpose of the present study is to evaluate the cost-effectiveness of a patient-reported outcome tool for symptom monitoring in patients undergoing treatment for advanced or metastatic cancer in Alberta compared to standard of care symptom monitoring from the perspective of the public payer in Alberta. Methods: A Markov model incorporating two health states (alive and dead) was used to calculate the incremental cost-effectiveness ratio of a web-based PRO tool for symptom monitoring compared to standard of care over a lifetime horizon. Clinical data was informed from the results of a North American randomized study of a similar web-based PRO tool for patients with metastatic cancer. Cost data was collected from provincial sources and prior Canadian publications. One-way sensitivity and probabilistic sensitivity analyses were performed to evaluate uncertainty in the model. A budget impact was performed to determine overall cost of implementation in the first three years. Results: In the base-case analysis, the PRO tool provided 2.17 QALY's at a total cost of 69, 030 compared to SOC arm yielding 1.92 QALY's at a total cost of 65, 670. The deterministic incremental cost per QALY gained was 13, 450. A probabilistic sensitivity analysis of 14 variables over 1000 iterations gave a probabilistic mean ICER of 13, 110. Overall cost of implementation for Alberta in the first three years was estimated at 1, 488, 160. Implementation however became cost-savings when savings for ER visits and hospitalizations were included. Conclusions: The results of this analysis show that for a cost increase of 3360 CAD, the use of a PRO tool for symptom monitoring yields an additional 0.25 QALYs. At a cost per QALY of ∼13, 450, this would be considered good value for money at the typically accepted Canadian standard of 50, 000 per QALY.